1980
DOI: 10.1021/ac50056a026
|View full text |Cite
|
Sign up to set email alerts
|

High performance liquid chromatographic separation of polycyclic aromatic hydrocarbons on microparticulate pyrrolidone and application to the analysis of shale oil

Abstract: A chemically bonded pyrrolidone substrate is used for the high performance liquid chromatographic separation of polycyclic aromatic hydrocarbons. The cyclic amide phase interacts electronically with the polycyclic aromatic hydrocarbons in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Comparison of these standards with the oil samples revealed that the shale aromatic fractions were composed mainly of 1-4 ring systems. The finding corroborated that previously noted by Mourey et al (15). Four major citrus limonoids are separated in less than 15 min on a nitrile (CN) column in the normal phase mode using a ternary solvent system.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Comparison of these standards with the oil samples revealed that the shale aromatic fractions were composed mainly of 1-4 ring systems. The finding corroborated that previously noted by Mourey et al (15). Four major citrus limonoids are separated in less than 15 min on a nitrile (CN) column in the normal phase mode using a ternary solvent system.…”
Section: Resultssupporting
confidence: 91%
“…The solvent system was chloroform-acetonitrile (95:5 v/v). However, because of the low sensitivity and the poor thermal stability of the refractive index detector, the method was abandoned in favor of a reverse phase system employing a water-methanol solvent system with chemically bonded nitrile (CN) column packing material and a variable wavelength UV detector set at 210 nm (15). There were several disadvantages with this procedure that made it unsuitable for…”
Section: Resultsmentioning
confidence: 99%
“…NMP, a dipolar aprotic solvent with a moderately high dielectric constant of 4.09D, seems to be an effective solvent to cleave some noncovalent bonds due to the strong interaction with polar sites in coals such as hydroxyl groups. Moreover, NMP has a good affinity for aromatic rings. , So, NMP can dissolve much more coal molecules and radicals than other good organic solvents for coal, for example, pyridine. Moreover, at 175−300 °C NMP dissolves them much more than at room temperature, and the resulting separation of the radicals from coal networks prevents retrogressive reactions such as radical additions to aromatic rings of coal networks, which would occur in a poor solvent.…”
Section: Resultsmentioning
confidence: 99%